Reverse Logistics Practices In Humanitarian Supply Chain Management: A Content Analysis - Yavuz Toraman; Fahriye Merdivenci; Makber Tekin (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In recent years, natural disasters associated with human-induced factors and climate changes have increased. The humanitarian supply chain (HSC) provides a practical and rapid response to these disasters and deals with the destruction that may occur due to disasters. The use of reverse logistics, one of the key supply chain processes for successful supply chain management, is becoming widespread in the supply chain. Its use in HSC is limited. Considering the aim of HSC to create positive effects on the population affected by disasters, it is essential for the sustainability of resources and processes that they adopt reverse logistics practices. In this context, the study aims to analyze the usage area of reverse logistics in HSC operations and show where it can be applied in the future. In line with the purpose of the study, the annual reports and publications of aid organizations operating in Turkey were analyzed using the content analysis method, and semi-structured interviews were conducted with experts in humanitarian aid organizations. It has been concluded that humanitarian aid organizations know reverse logistics processes and have areas of use in their applications.